Airline pilots’ perceived operational benefit of a startle and surprise management method: a qualitative study - Vlaskamp, Daan; Landman, Annemarie; van Rooij, Jeroen; Li, Wen-Chin; Blundell, James (SciTePress - Science and Technology Publications, 2024)
Startle and surprise can impair pilot performance and jeopardize flight safety. Self-management methods have been developed by the industry to address this acute source of stress, however, qualitative insights from pilots describing the quality of these methods are lacking. Ten semi-structured interviews with airline pilots, who had been taught a self-management method, were analyzed using thematic analysis). Pilots considered the method useful and reported positive effects (e.g., decrease in stress) when applying the method during operations. Pilots reported that the method was not often performed in full; specific steps were employed based on perceived benefit. Establishing fellow pilot status and situation awareness was considered most important, addressing own physical startle symptoms (e.g., muscle tension) were deemed less important. Pilots reported an urge to “act” rather than use the method, which is expected as the method aims to induce a pause and mitigate erroneous impulsi ve decisions. Barriers to applying the method included the difficult recognition of startle and surprise, and situational context. Suggested improvements for training dealt with recognition and sharing experiences from peers. The findings of the research provide directions for pilot training for startle and surprise. Future research will explore these pilot perceptions in a larger representative sample.
Keywords: 3504 Commercial Services; 35 Commerce, Management, Tourism and Services